Biochemical characterization of foot-and-mouth disease virus - Nath, Rita; Prasad, Ram Lakhan; Sarma, Sankar (The Indian Journal of Animal Sciences, 2012)
The present study was carried out to determine the molecular weight and mobility of the proteins present in the FMD virus. FMD trivalent vaccine and FMD infected serum samples were used for the study. The standard SDS-6H of known proteins was used for calculating the molecular weight of different proteins.The molecular weight of the FMD viral proteins 1 and 2 were 101 and 62 K Da and mobilities were 0.268 and 0.521 respectively. Seven distinct bands segregrated in control and FMD affected serum samples. The bands in the control sample from the top of the gel were identified as g globulin, ß globulin, unidentified protein, heptoglobin, albumin, a2 globulin and unidentified protein. Their molecular weights were 150, 140, 120, 100, 60, 48 and 33 K Da and mobilities were 0.094, 0.126, 0.186, 0.268, 0.536, 0.631 and 0.805 respectively. In the FMD affected sample, g –globulin was undetectable but an extra band was noticed in the infected serum sample which was identified as the FMD viral protein.